Mahasiswa Sebagai Role Model Dalam Memperjuangkan Hak Atas Kebebasan Berekspresi: Belajar Dari Uksw Berdasarkan Visi Magistrorum Et Scholarium - Putri, Annasthazia Iola; Lase, Vlorencus Jupinter (Publikasi Indonesia, 2025)
This study examines the contradiction between the role of university students as role models in defending freedom of expression and the reality of Indonesia’s higher education system, which remains entrenched in hierarchical structures and a culture of conformity. Using a qualitative research method through literature review and descriptive analysis, this study reveals how Indonesian students face a dilemma: on one hand, they are expected to be agents of social change; on the other, they must operate within a system that restricts their freedom of expression. The findings indicate that this contradiction creates structural tensions that weaken the effectiveness of students as role models for freedom of expression. This study recommends the need for reforms toward a more democratic and participatory higher education system to support the role of students as agents of social change. Background: Historically, university students have played a crucial role as agents of social and political change in Indonesia. From the independence movement to the Reformasi era in 1998, students have consistently been at the forefront of advocating for various social issues, including the right to freedom of expression. This role has positioned them as role models within society in promoting democratic values and human rights. However, the current reality within Indonesian higher education institutions reveals a fundamental contradiction. The system, which still upholds hierarchical authority and emphasizes conformity, often restricts students’ space for expression. The top-down academic structure, strong seniority culture, and institutional control mechanisms create a paradoxical environment for students who are expected to be champions of freedom of expression. Objective: To examine the contradiction between the role of university students as role model s in advocating for freedom of expression and the hierarchical and conformist structure of Indonesia’s higher education system. Methods: This research employs a qualitative method by integrating a conceptual approach, a statute-based (legal) approach, and a case-based approach. Results: Normatively, students are positioned as agents of change and role models in upholding freedom of expression—in their thoughts, attitudes, and actions. However, in practice, Indonesia’s higher education system, dominated by hierarchical values and a culture of conformity, becomes a structural barrier that limits such freedom. This contradiction leads to a range of multidimensional impacts. Conclusion: The contradiction between the ideal role of students as role models of freedom of expression and the hierarchical nature of the higher education system has generated psychological, social, and intellectual consequences that hinder the development of their critical thinking. Therefore, structural and cultural reforms within university environments are essential to creating an inclusive, democratic, and dialogic academic space.